MODELLING AND EXPERIMENTAL STUDY OF ENERGY FEED SUSPENSION SYSTEM FOR ELECTRIC VEHICLE - Wang, Xiumei (International Journal of Mechatronics & Applied Mechanics, 2019)
In order to solve the deterioration of the contradiction between ride comfort and handling stability of wheel-side-driven electric vehicle, the torque control of wheel-driven electric vehicle is studied, the influence of vertical excitation of wheel-driven motor on power performance and energy-feeding characteristics of electric vehicle is analyzed, and the energy-feeding law and characteristics of energy-feeding suspension are discussed. The effective methods that can improve the safety, relaxation, and energy-feeding characteristics of wheel-driven electric vehicle through the control of electromagnetic active suspension are proposed. Through the suspension simulation model and energy recovery simulation model, under the guidance of sliding mode control theory and Drosophila optimization algorithm theory, a control algorithm with excellent control effect is designed for semi-active suspension system design, and the effectiveness of the algorithm is verified by simulation analysis. The simulation model is built by using the input signal of various working conditions as the road input, and the simulation results of the control algorithm are compared with other control algorithms. The results show that the designed control algorithm can effectively improve the vibration reduction effect of suspension compared with other control algorithms. At the same time, the energy recovery efficiency of the energy-fed damper will be investigated through the simulation experiment of the energy-fed damper. Therefore, the study can provide theoretical basis and technical support for the development of wheel-side-drive electric vehicles with independent intellectual property rights.